Patè Olive Cake: Possible Exploitation of a By-Product for Food Applications - Tufariello, Maria; Durante, Miriana; Veneziani, Gianluca; Taticchi, Agnese; Servili, Maurizio; Bleve, Gianluca; Mita, Giovanni (Frontiers in Nutrition, 2019)
Patè Olive Cake (POC) is a new by-product derived from recently introduced new decanters in the olive oil production process. POC, is essentially composed of water, olive pulp and olive skin, and is rich in several valuable bioactive compounds. Moreover it still contains about 8-12 % residual olive oil. We characterised the main bioactive compounds in POC from black olives (cv. Leccino and Cellina di Nardò) and also verified the biotechnological aptitude of selected yeast and lactic acid bacteria from different sources, in transforming POC into a new fermented product. The strategy of sequential inoculum of Saccharomyces cerevisiae and Leuconostoc mesenteroides was successful in driving the fermentation process. In fermented POC total levels of phenols were slightly reduced when compared with a non-fermented sample nevertheless the content of the antioxidant hydroxytyrosol showed increased results. The total levels of triterpenic acids, carotenoids and tocochromanols results were almost unchanged among the samples. Sensory notes were significantly improved after fermentation due to the increase of superior alcohols, esters and acids. The results reported indicate a possible valorisation of this by-product for the preparation of food products enriched in valuable healthy compounds.